Morphometric Analysis of Variations in Pattern of Talar Articular Facets on Calcaneum in North-West India - Dang , B; Rathee , S K; Gupta , S; Vashist, Y K (Journal of Indian Academy of Forensic Medicine, 2023)
Calcaneum, the largest tarsal bone forms joint with Talus (Talocalcaneal joint). The superior surface of calcaneum shows three facets for  talus. Patterns of facets are variable in different populations. Knowledge of the facets is important for orthopaedic surgeons in correction of  foot deformities, as facet number is an important factor in subtalar joint stability and formation of osteophytes in osteoarthritis. The  objective of the present study was to identify the patterns of talar facets on calcaneum in North-West India population and their comparison  with other population of the world. For the present study; 100 calcanei of unknown age and sex were used. The calcanei were retrieved  from the department of Anatomy, at a tertiary care hospital and medical college, in Haryana. The current study will focus on talar articular  facets on calcanei. Patterns of talar articular facets on calcanei were observed as described by Bunning and Barnett et al. Present study  revealed that pattern I and II were commonly present in the North West population, and accounted for 83% and 16% respectively. The  North West population presented Pattern I as the most common pattern as compared to the European population where pattern II was  reported as the most common pattern, so variation in the facet pattern between races demand a modification of surgical technique of  calcaneal osteotomy to meet the needs of a particular population.
Keywords: Calcaneum; Talar facets; Arthritis